Who is afraid of punishing aggressors?: On the double-track approach to international criminal justice - Zolo, Danilo (Journal of international criminal justice, 2010)
Since 1947, no alleged crime of aggression has ever been prosecuted, in spite of the many instances in which states have committed acts of aggression with the Security Council sometimes deeming an act to be such. A dual system of international criminal justice has taken shape slowly. Crimes consisting of serious violations of jus in bello, that is, war crimes, usually considered less egregious than the crime of aggression, have been severely prosecuted and punished, in particular by the International Criminal Tribunal for the former Yugoslavia (ICTY). Yet, the supreme international crime aggressive war mostly committed by political and military authorities of major powers, has been ignored and its perpetrators still occupy the summit of international power undisturbed